2017
DOI: 10.1515/jmbm-2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Review on effect of chemical, thermal, additive treatment on mechanical properties of basalt fiber and their composites

Abstract: Basalt fiber is emerging out the new reinforcing material for composites. To overcome some of the disadvantages of fibers such as poor bonding to polymers, low thermal stability and high moisture absorption fiber characteristics are modified with chemical, thermal and additive treatments. Chemical treatment corrosive resistance to alkali and acid were investigated which were used to clean and modify the surface of fiber for higher bonding with resins. To improve the thermal stability and reduce moisture uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…An elemental analysis reveals an increase in the Na content by 0.7%, Al by 1.6%, Fe by 1.5%, Mg by 0.63%. Thus, it has been proved that the structure of silicon oxide is resistant to acids, and metal ions change places with hydrogen atoms and pass into an acid solution in accordance with the reaction [42].…”
Section: Acid Solutionsmentioning
confidence: 98%
See 2 more Smart Citations
“…An elemental analysis reveals an increase in the Na content by 0.7%, Al by 1.6%, Fe by 1.5%, Mg by 0.63%. Thus, it has been proved that the structure of silicon oxide is resistant to acids, and metal ions change places with hydrogen atoms and pass into an acid solution in accordance with the reaction [42].…”
Section: Acid Solutionsmentioning
confidence: 98%
“…Alkaline solutions have the greatest impact on the structure and properties of BF [9,10,18,23,24,27,33,42,45].…”
Section: Alkali Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosa et al [13] also used rice husk our as reinforcement in same matrix material by melt extrusion process and concluded that there is decrease in tensile strength with increase in reinforcement. Many researchers used polyethylene matrix with rice husk and reported signi cant e ect of reinforcement on mechanical properties of composite material [14][15][16][17][18][19]. Epoxy resin and wood our based composite was developed and its tribological behavior was studied by Dwivedi et al [20] and analyzed that there are e ective increases in load carrying capacity and decrease in wear resistance of matrix material.…”
Section: Introductionmentioning
confidence: 99%
“…The broken basalt is added into a furnace and melted at 1450°C-1500°C, and then leaked from a platinumrhodium alloy wire drawing plate to form continuous filament [1][2][3][4][5]. BFs are eco-friendly fibers, which attract lots of attention from researchers and constructors because of their strong tensile strength, high elastic modulus, high abrasion strength, good temperature-resistance, excellent heat and sound insulation, good chemical stability and so on [6][7][8][9]. Therefore, BFs are called as a green industrial material in 21 st century.…”
Section: Introductionmentioning
confidence: 99%